Cancer: A disease at the crossroads of trade‐offs. (26th December 2016) - Jacqueline, Camille; Biro, Peter A.; Beckmann, Christa; Moller, Anders Pape; Renaud, François; Sorci, Gabriele; Tasiemski, Aurélie; Ujvari, Beata; Thomas, Frédéric
Abstract: Central to evolutionary theory is the idea that living organisms face phenotypic and/or genetic trade‐offs when allocating resources to competing life‐history demands, such as growth, survival, and reproduction. These trade‐offs are increasingly considered to be crucial to further our understanding of cancer. First, evidences suggest that neoplastic cells, as any living entities subject to natural selection, are governed by trade‐offs such as between survival and proliferation. Second, selection might also have shaped trade‐offs at the organismal level, especially regarding protective mechanisms against cancer. Cancer can also emerge as a consequence of additional trade‐offs in organisms (e.g., eco‐immunological trade‐offs). Here, we review the wide range of trade‐offs that occur at different scales and their relevance for understanding cancer dynamics. We also discuss how acknowledging these phenomena, in light of human evolutionary history, may suggest new guidelines for preventive and therapeutic strategies.